(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the analysis of basic provisions of theorists of division of the power into branches is given. In particular positions of classics of a political and legal thought are stated: Sh.L. Montesquieu, J. Locke, Zh.Zh. Russo. The theory of division of the authorities has gained the further development, as in theoretical works of thinkers of the next years, and practical activities of the states which have apprehended this principle in creation of the government. Key words: Branches, division, power, state.